EFFECT OF ADDITION FENNEL OIL AND TARTARIC ACID ON REGIME AND BURNING RATE OF CPKO DROPLETS - Dwiantoko, Putra; Wardana, I.N.G; Wijayanti, Widya; Sasmoko, Sasmoko (International Journal of Mechanical Engineering Technologies and Applications, 2026)
This study examines the effect of combustion speed on crude palm kernel oil (CPKO) droplets with and without the addition of additives and catalysts to the mixture. As is known, the main component of CPKO is palmitic acid, which has a 16-carbon chain. This characteristic results in a relatively slow combustion rate of CPKO. In this study, the author added fennel oil as a bio-additive and tartaric acid as a catalyst to compare their effects on combustion speed. Fennel oil contains anethole, which has a conjugated cyclic ring capable of generating a magnetic field that can weaken the molecular bonds of CPKO. Meanwhile, tartaric acid acts as a catalyst that accelerates the combustion process due to its high electronegativity, which can disrupt the glycerol bonds in CPKO. The results of the study indicate a positive effect of adding fennel oil and tartaric acid as additives, with concentrations of 100, 200, and 300 ppm, on combustion speed.